Upaya Bersama Rehabilitasi melalui Penanaman Mangrove dalam Mitigasi Bencana di Wilayah Pesisir Kota Sorong - Ibal, La; Murni; Abu, Nur (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The coastal areas of Sorong City face many risks, including tidal flooding and erosion. The solution to the problem of facing this challenge is to restore and protect the mangrove ecosystem. The aim of this service is to increase public understanding of the importance of planting mangroves as part of disaster mitigation efforts in the coastal areas of Sorong City. Involvement in this activity includes community participation, traditional leaders, local government, students, and academics. The method used is descriptive-qualitative. The result of this service is that the efforts carried out include providing information to the residents of Klawalu Village about the importance of mangroves in marine ecosystems, steps to prevent abrasion, and supporting the planting of mangroves along the coastline. Positive responses were obtained from residents who enthusiastically planted mangroves and hoped that through this activity, the risk of abrasion could be minimized and degradation in coastal areas, where the community lived, could be reduced.